A magnetically recyclable dual step-scheme Bi2WO6/Fe2O3/WO3 heterojunction for photodegradation of bisphenol-A from aqueous solution. Issue 6 (December 2021) - Shandilya, Pooja; Guleria, Ankita; Fang, Baizeng
Abstract: An efficient, visible light active, non-toxic, magnetically separable, and highly efficient dual step-scheme (S-scheme) Bi2 WO6 /Fe2 O3 /WO3 (BFW) heterojunction were fabricated by ultrasonic-assisted wet impregnation method. The morphology, chemical states, surface area, optical and electrochemical characteristics were examined by SEM, TEM, EDX, FTIR, BET, XRD, UV-Vis-DRS along with PL analysis. The S- scheme type charge transfer and mineralization process in BFW heterojunction were in-depth investigated by electrochemical studies, HPLC, LC-MS, and XPS analysis. The superoxide and hydroxyl radicals generated on BFW heterojunction photodegraded 99% of bisphenol-A which was established by trapping experiments and ESR techniques. Further, effect of catalyst dosage, BPA concentration, initial pH, and the presence of ions on photodegradation were also investigated. As reflected in VSM analysis, the strong-magnetic behaviour allows magnetic separation of heterojunction which is recyclable up to 7 catalytic runs. Significant photocurrent density and lower charge transfer resistance at the interface demonstrate higher efficiency of BFW. Hence, we believe this work furnish new insights for fabricating a novel S-scheme based heterojunction for environmental remediation. Graphical Abstract: ga1 Highlights: Bi2 WO6 /Fe2 O3 /WO3 heterojunction fabricated by ultrasonic assisted wet impregnation method. The magnetically recyclable heterojunction display efficient charge separation. Bi2 WO6 /Fe2 O3 /WO3 photodegraded 99% of bisphenol-A in 30 min. S-scheme charge migration is established by XPS, trapping experiment and ESR. Novel Bi2 WO6 /Fe2 O3 /WO3 is a promising heterojunction for environmental remediation.